Village empowerment by increasing reading interest to children in Sukadami village - Aulia Nurannisa; Aulia Shabrina Fitri; Muhammad Farhan Nurpratama (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2024)
Reading is one of the most important activities in human life. Aside from being a means of entertainment, reading has many benefits that can improve one's quality of life. This is in line with the UN agenda, namely Sustainable Development Goals (SDGs), which strive to improve the quality of life for everyone throughout the world. The existence of SDGs point 4 related to quality education has encouraged UPI 2023 thematic Community Services students to set up a reading corner in Sukadami Village. This is based on a lack of interest in reading and the provision of existing facilities in Sukadami Village. The location for establishing this reading corner is in the Karang Taruna secretariat room of Sukadami Village. This placement is considered due to its strategic location so that it is easily accessible by anyone. Methods of implementation include (1) collecting various types of reading materials, (2) establishing reading corners, and (3) socializing the urgency of reading. With this work program it is hoped that it can stimulate interest in reading in the community in Sukadami Village. Another goal is to regenerate post-corona social interaction so that a harmonious and caring society can be re-formed. The end result of the implementation of this program is the success of channeling interest in reading by providing a special place for reading.   Abstrak Membaca merupakan salah satu aktivitas terpenting dalam kehidupan manusia. Selain sebagai sarana hiburan, membaca mempunyai banyak manfaat yang dapat meningkatkan kualitas hidup seseorang. Ini sejalan dengan agenda PBB yakni Sustainable Development Goals (SDGs) yang berusaha untuk meningkatkan kualitas hidup setiap orang di seluruh dunia. Adanya SDGs poin 4 terkait pendidikan berkualitas ini mendorong mahasiswa KKN tematik UPI 2023 untuk mendirikan pojok baca di Desa Sukadami. Hal ini didasari dengan kurangnya minat baca dan penyediaan sarana yang ada di Desa Sukadami. Adapun lokasi pendirian pojok baca ini berada di ruangan sekretariat Karang Taruna Desa Sukadami. Penempatan ini dipertimbangkan berkat lokasinya yang strategis sehingga mudah dijangkau oleh siapapun. Metode pelaksanaannya antara lain (1) pengumpulan berbagai jenis bahan bacaan, (2) pendirian pojok baca, dan (3) sosialisasi urgensi membaca. Dengan adanya program kerja ini diharapkan dapat menggairahkan minat membaca masyarakat di Desa Sukadami. Adapun tujuan lainnya yakni dapat menumbuhkan kembali interaksi sosial pasca korona sehingga terbentuk kembali masyarakat yang rukun dan saling peduli. Hasil akhir dari pengadaan program ini yakni keberhasilan penyaluran minat baca dengan menyediakan suatu tempat khusus membaca. Kata Kunci: Desa Sukadami; kuliah kerja nyata; perpustakaan; pojok membaca